Perlindungan Hukum terhadap Pekerja dalam Pelaksanaan Hubungan Industrial - tanti kirana utami; Ahmad Hunaeni Zulkarnaen (Faculty of Law, Universitas Padjadjaran, 2016)
Sistem hukum hubungan industrial Pancasila berupaya menempatkan pekerja/buruh dengan pengusaha termasuk didalamnya pemerintah dalam kedudukan yang proporsional. Eksistensi atau keberadaan pekerja dalam hubungan industrial harus dilindungi oleh pengusaha dengan diperlakukan sebagai mitra kerja. Untuk itu, pelaksanaan hubungan industrial sebaiknya merujuk ke dalam sistem demokrasi ekonomi Pancasila, yakni suatu sistem demokrasi ekonomi sebagai hasil pengejawantahan dari konsep integralistik Pancasila.Legal Protection of the Workers in the Implementation of Industrial Relations AbstractThe legal system of industrial relations based on Pancasila attempts to place workers or laborers with employers, including the government, in a proportional position. The existence or presence of workers in industrial relations should be protected by the employer, in which workers are to be treated as a partner. Therefore, the implementation of industrial relations should refer to the system of economic democracy of Pancasila, namely a system of economic democracy as the embodiments of the integrative concept of Pancasila.DOI: https://doi.org/10.22304/pjih.v3n2.a10